2003
DOI: 10.1126/science.1082795
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Sleep and Behavioral Adaptability in NPAS2-Deficient Mice

Abstract: Animal behavior is synchronized to the 24-hour light:dark (LD) cycle by regulatory programs that produce circadian fluctuations in gene expression throughout the body. In mammals, the transcription factor CLOCK controls circadian oscillation in the suprachiasmatic nucleus of the brain; its paralog, neuronal PAS domain protein 2 (NPAS2), performs a similar function in other forebrain sites. To investigate the role of NPAS2 in behavioral manifestations of circadian rhythm, we studied locomotor activity, sleep pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
272
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(298 citation statements)
references
References 49 publications
21
272
2
3
Order By: Relevance
“…Mutations in either the FBXL21 or FBXL3 genes can lead to a dysfunction of circadian rhythm oscillations and lead to significant behavioral disturbances in individuals and alterations in their sleeping patterns; moreover the absence of FBXL21 causes a short-period phenotype in both mice and cells (Hirano et al, 2013;Yoo et al, 2013 (Bromundt et al, 2011); which is further supported by a microarray study which found a significant downregulation of the circadian pacemaker gene PER1 in the postmortem temporal cortex of schizophrenia patients compared to healthy controls (Aston et al, 2004). Furthermore, an animal model study has shown dysfunction in the synchronization of circadian rhythms between brain cell networks involved in sleep-wake regulation and cognition (Dudley et al, 2003). Overall this suggests that alterations in circadian rhythms are present in schizophrenia, and that polymorphisms in the FBXL21 gene in addition to the FBX3 gene, could be involved in the circadian cycle disturbances that have been observed in schizophrenia (Mansour et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…Mutations in either the FBXL21 or FBXL3 genes can lead to a dysfunction of circadian rhythm oscillations and lead to significant behavioral disturbances in individuals and alterations in their sleeping patterns; moreover the absence of FBXL21 causes a short-period phenotype in both mice and cells (Hirano et al, 2013;Yoo et al, 2013 (Bromundt et al, 2011); which is further supported by a microarray study which found a significant downregulation of the circadian pacemaker gene PER1 in the postmortem temporal cortex of schizophrenia patients compared to healthy controls (Aston et al, 2004). Furthermore, an animal model study has shown dysfunction in the synchronization of circadian rhythms between brain cell networks involved in sleep-wake regulation and cognition (Dudley et al, 2003). Overall this suggests that alterations in circadian rhythms are present in schizophrenia, and that polymorphisms in the FBXL21 gene in addition to the FBX3 gene, could be involved in the circadian cycle disturbances that have been observed in schizophrenia (Mansour et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…NPAS2 forms heterodimers with BMAL1 and then transcriptionally activates expression of the circadian genes per and cry, which are required for maintaining biological rhythms in many organisms [6,7]. In animal studies, altered circadian patterns of sleep and behavioral adaptability have been observed in NPAS2-deficient mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that the molecular regulators of the circadian clock have different influences on sleep patterns. For example, in NPAS2-deficient mice, non-REM sleep is reduced and more sleep time is required following sleep deprivation [98]. But the absence of Cry1, 2 is characterized by hypersomnolence [99].…”
Section: Clock Gene Differencementioning
confidence: 99%